2002
DOI: 10.1097/00007691-200212000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Digoxin in Pediatric Patients

Abstract: Digoxin pharmacokinetics were studied in a pediatric population with an age range of 6 days to 1 year using the population pharmacokinetic approach. Digoxin data were analyzed by mixed-effects modeling according to a one-compartment steady-state pharmacokinetic model using NONMEM software. The final model selected for the population prediction of digoxin clearance in pediatric patients was as follows: [equation: see text] Individual empirical Bayesian estimates were generated on the basis of the population est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…It is well recognized that renal blood flow, the glomerular filtration rate, and tubular secretion change rapidly within the first year of life 6 . The correlation between some other covariates, such as body weight and age, with the pharmacokinetic (PK) parameters of many drugs is also suggested in the literature 7 , 8 . So there is good reason to believe that meropenem PK in pediatric patients is closely related with some potential covariates.…”
mentioning
confidence: 99%
“…It is well recognized that renal blood flow, the glomerular filtration rate, and tubular secretion change rapidly within the first year of life 6 . The correlation between some other covariates, such as body weight and age, with the pharmacokinetic (PK) parameters of many drugs is also suggested in the literature 7 , 8 . So there is good reason to believe that meropenem PK in pediatric patients is closely related with some potential covariates.…”
mentioning
confidence: 99%
“…10,19,20 This is quite logical as the renal function changes with age in neonates. 22 Such a relationship between age and digoxin clearance could not be observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [1,2,7] reported that a one-compartment model and the first-order kinetics process could describe the time course of digoxin steady state concentrations in plasma. In this paper, a one-compartment open model was selected as a population structural PK model.…”
Section: Structural Pharmacokinetic Modelmentioning
confidence: 99%
“…Because of its low therapeutic index, narrow safety range and strong side effects, toxicity may also be caused by routine dosage [1][2][3][4] . Elderly patients with heart failure are more susceptible to toxicity because their impaired renal function may cause the clearance of digoxin to decrease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation